Augmented Reality (AR)-Based Learning Innovation To Improve Student Understanding Subjects - Laia, Putrawan Saleh; Halawa, Zun Kelvin Eferistus Albers; Ndruru, Intan Hartini; Gulo, Suryani; Zega, Sailas Mardianti; Gulo, Jernita; Waruwu, Yaredi (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
This study investigates the implementation of Augmented Reality (AR) technology as an innovative learning tool to enhance student understanding across various subjects. The integration of AR in educational settings has shown promising potential in creating interactive and immersive learning experiences. Through a systematic analysis of AR implementation in classroom settings, this research examines its effectiveness in improving student comprehension, engagement, and learning outcomes. The study employs a mixed-method approach, combining quantitative assessment of student performance with qualitative evaluation of learning experiences. Results indicate that AR-based learning significantly improves student understanding, with particular effectiveness in subjects requiring spatial visualization and complex concept comprehension. This research contributes to the growing body of knowledge on educational technology integration and provides practical insights for educators seeking to implement AR-based learning solutions.